- - Ladrière, Jean (Acta Bioethica, 2000)
The following text shows us the reflections made by Jean Ladrière concerning the sense and meaning of bioethics in the context of what is known today as the growth of “applied ethics”. From the first considerations he refuses accepting the idea that “regional ethics” limits itself to translate –into the sphere of concrete situations– general principles, since this would be equivalent to ignore creativity, innovative possibilities and the risks involved in the action in its permanent determination of existence. Establishing the need of inaugurating reflections concerning proposed themes –from the space filled and legitimized by bioethical drive– he attempts to show the complicity between bioethics and ethics, as well as to puzzle out the specific way in which bioethics respond to the demands of producing regulations, that in particular are consequence of the challenges of human and techno-scientific actioning. Jean Lardrière’s argumentation briefly explains issues addressed throughout his research and which may seem too hermetic to the unprepared reader. The subject of techno-science was analyzed by Jean Ladrière in his book Les enjeux de la rationalite (1977) and in many other publications; the issue of existence and its relationship with the sense in L’articulation du sens (1971, volume 1; 1985, volume 2), and the topic of ethics and the ethical dimension of existence in L’ethique dans l’ univers de la rationalité (1997). It is relevant pointing out that as translator of this text, I tried to use Spanish issues of some of the authors quoted but in front of differences related to certain terms –showing disparity of interpretation– I decided to translate them directly from Jean Ladrière’s text.